PENGARUH KECEMASAN DI PERPUSTAKAAN TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PEMUSTAKA PADA PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA - Rahayu, Annisa; Rohmadi, Djazim (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This research examines how anxiety influences fulfilling users' information needs at the UIN Sunan Kalijaga Yogyakarta Library. This research uses a quantitative method using a sample of 100 active student respondents at UIN Sunan Kalijaga Yogyakarta with a purposive sampling technique. The analysis results show that the anxiety variable's coefficient of determination on meeting needs is 0.642. These results show that the influence of anxiety on fulfilling information needs in the UIN Sunan Kalijaga Yogyakarta Library is 64.2%. The nature of the impact of these two variables is positive, where the simple linear regression equation is Y = 4.203 – 0.334X. The results of hypothesis testing show a rcalculate of 13.268. These results show results that are greater than. This research concludes that library anxiety significantly and positively influences meeting information needs.